Inhibitive Action of Sulfide Ions on Corrosion and Enhancing Charge‐Discharge Efficiency of Zinc and Zinc‐Indium Alloy as Anode for Alkaline Batteries - Hany M. Abd El‐Lateef; Mahmoud Elrouby; Hoda A. El‐Shafy Shilkamy; Abd El‐Rahman El‐Sayed (ChemElectroChem, 2024)
Abstract The obtained data reveal that the coverage of surface (θ) and protection efficiency (η%) for the studied electrodes increases gradually as the inhibitor concentration increases. Tafel plot is carried out at variant temperatures in the investigated basic electrolyte containing 1×10−1 M of S ions. This study reveals that the activation energy barrier of the studied alloy is higher than that of pristine zinc anode at a fixed inhibitor concentration. It is observed that ▵Goads. and η% values rise with rising solution temperature, indicating that S ions adsorption on the studied electrode surfaces occurs by a chemisorption mechanism. Other calculations are made for the additional thermodynamic parameters such as ▵Hoadsand ▵Soads. The zinc anodes get more efficient when S ions are added to the solution, considerably decreasing electrochemical polarization. In addition, the presence of indium sulfide improves the exposed surface area of the alloy, supplying additional improvement in charge‐discharge efficiency. Density functional theory (DFT) is utilized to extract the quantum data to acquire a deeper understanding of the chemical processes between sulfide ions at the interface.